The Effectiveness of Non-Invasive Brain Stimulation Alone or Combined with Cognitive Training on the Cognitive Performance of Patients With Traumatic Brain Injury: Α Systematic Review. (21st June 2021) - Nousia, Anastasia; Martzoukou, Maria; Liampas, Ioannis; Siokas, Vasileios; Bakirtzis, Christos; Nasios, Grigorios; Dardiotis, Efthimios
Abstract: Objective: The present study reviewed published evidence on the effectiveness of non-invasive brain stimulation (NIBS) on the cognitive performance of patients with Traumatic brain injury (TBI). Method: A systematic search of the PubMed and Google Scholar databases was carried out. Randomized Controlled Studies published before March 2020 were included. Methodological evaluation was performed based on the Risk of Bias Cochrane tool. A total of 10 placebo-controlled studies fulfilled the inclusion criteria and were involved in the qualitative analysis, two assessing NIBS combined with cognitive training (CT) and eight evaluating NIBS alone. Results: All but one retrieved article were appraised as of high-risk of bias (one paper was assessed as of unclear-risk owing to considerable underreporting). With the potential exception of attention, our findings were not indicative of a superior efficacy of NIBS-CT to CT alone, regarding the improvement of any of the rest assessed cognitive deficits. Executive function, processing speed, attention, working, and visuospatial memory were only occasionally found to benefit from NIBS alone compared to sham therapy (only one study reported relevant benefits per neuropsychological outcome). Verbal memory and verbal fluency (phonemic-semantic) were consistently found not to benefit from NIBS. Depression measures were the only outcomes associated with a beneficial effect of NIBS in more than one article. Conclusion: Our findings did not provide sufficient high-quality evidence to support the exclusive use of NIBS or combined NIBS-CT to improve any impaired cognitive function in TBI patients. Owing to the suboptimum methodological quality of published studies, additional research is of potential value.